X-ray computed tomography analysis of pore deformation in IN718 made with directed energy deposition via in-situ tensile testing. (1st December 2022) - Kafka, Orion L.; Yu, Cheng; Cheng, Puikei; Wolff, Sarah J.; Bennett, Jennifer L.; Garboczi, Edward J.; Cao, Jian; Xiao, Xianghui; Liu, Wing Kam
Abstract: Directed energy deposition (DED) is a metal additive manufacturing technique often used for larger-scale components and part repair. It can result in material performance that differs from conventionally processed metal. This work studies spatial and orientation-based differences in tensile properties of nickel-based alloy IN718 using in-situ x-ray computed tomography to observe internal pore populations. Anisotropy and spatial variability in mechanical properties are shown while the evolution of pore shape during deformation is measured. Measured pore deformation is compared to predict deformations simulated using a computational crystal plasticity scheme, which provides insight, through inverse modeling, to the grain orientation in which the pore resides. The measurements provide a high fidelity method to compare experimental and computational approaches to pore deformation studies. Pore deformation measurements show that pores tend to grow and elongate in the direction of loading, consistent with ductile deformation and likely deforming with the material. Generally, the pore defects observed in this material (not from lack-of-fusion) do not cause so-called premature failure, and fully developed necking occurs prior to fracture. Highlights: In-situ x-ray computed tomography measurement of pore deformation. Mechanical testing of directed energy deposition IN718 thin walls. Analysis of individual and average pore response to applied load. Inverse computational crystal plasticity modeling of pore shape evolution can identify local grain orientation. Large, comprehensive data set published alongside manuscript to support open data initiatives.